Determination of trophic status and carrying capacity of floating net cages in Jatigede Reservoir - Kristina Marsela; Dadan Sumiarsa; Denny Kurniadie (Jurnal Akuakultur Indonesia)
Aquaculture activities with floating net cages are essential to increase fishery production. However, The fish cages in the Jatigede Reservoir are illegal because they are against local government regulations. However, the people affected by the dam's construction still maintain it for economic reasons. Therefore, it is necessary to conduct research to address these problems by determining the carrying capacity of aquaculture and evaluating the trophic status of the waters. Determination of the carrying capacity of fish farming in the Jatigede Reservoir was conducted using the Beveridge method. by calculating the remaining phosphorus still available in the Jatigede Reservoir and evaluating the trophic state index based on three indicators: transparency, total phosphorus, and chlorophyll-a. The sampling was carried out by purposive sampling method. The calculation results show that the condition of the Jatigede Reservoir was eutrophic to hypertrophic with a trophic state index (TSI) value of 66-71. The results of calculating the carrying capacity of cage aquaculture using class 3 water quality standards. Indicate that Jatigede Reservoir waters can still increase fish production by 7,140.25 tons of fish/year, provided that fish replace the primary fish commodities cultivated.